Kesalahan Terjemahan Dalam Teks Alih Bahasa Inggris-Indonesia Serial Original Netflix: The Queen’s Gambit - Putri Sutaji, Tirta Ningtyas Alifia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to identify translation errors from English to Indonesian in the Netflix Original Series. The data in this study were taken from the subtitles of the Netflix Original Series entitled